2013
DOI: 10.1016/j.agrformet.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of thermography for plant water stress detection in citrus and persimmon trees

Abstract: The feasibility of using canopy temperature (T c ) measured with a hand-operated infrared thermographic camera as a water stress indicator was evaluated in the field during two seasons on citrus and persimmon trees subjected to different levels of deficit irrigation. In both species, which differ in leaf anatomy and stomatal response to environmental conditions, T c was compared with midday stem water potential ( s ) measurements. In persimmon trees, leaf stomatal conductance (g s ) was also measured. T c was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 28 publications
12
65
2
5
Order By: Relevance
“…The differences between sunlit and shadow zones with FRT and SDM coincided with those obtained by Jones et al [21], who found that the shadow side of the canopy was particularly appropriate for row or tree crops. In the case of nadir view, the results obtained with the EBT and FRT filters coincided with those obtained by Ballester et al [40], who found that significant differences were detected in the nadir zone between stressed and non-stressed plants when lateral images did not detect differences between them. However, Ochagavia [19] found that r 2 values in vineyards with temperature values recorded from the lateral canopy side were higher than temperature values measured from the nadir position.…”
Section: Discussionsupporting
confidence: 78%
“…The differences between sunlit and shadow zones with FRT and SDM coincided with those obtained by Jones et al [21], who found that the shadow side of the canopy was particularly appropriate for row or tree crops. In the case of nadir view, the results obtained with the EBT and FRT filters coincided with those obtained by Ballester et al [40], who found that significant differences were detected in the nadir zone between stressed and non-stressed plants when lateral images did not detect differences between them. However, Ochagavia [19] found that r 2 values in vineyards with temperature values recorded from the lateral canopy side were higher than temperature values measured from the nadir position.…”
Section: Discussionsupporting
confidence: 78%
“…Wang & Gartung (2010) found that the midday Tc-Ta in a water-stressed, deficit irrigation treatment of peach trees were in the range 5-7 °C. The maximum Tc difference between deficit-irrigated and control trees observed in persimmon trees was 4°C (Ballester et al 2013), while the maximum Tc difference between drought year and normal year was about 1 °C in the TRF. The possible reasons for the lower Tc-Ta found in the tropical rain forest include: (i) tree species in the tropical rain forest are highly diversified in canopy architecture.…”
Section: Interannual Variations In Tc-tamentioning
confidence: 96%
“…The temperature of the branches and selfshaded leaves were not measured, resulting in an underestimation of the actual Tc. This might be a general problem in natural forests (Scherrer et al 2011). (ii) Most studies dealing with drought effects on Tc on crops have worked with precise irrigation treatments for determining the Tc to the difference in drought stress level, such as irrigated 50% evapotranspiration and irrigated 25-33% (Campbell & Norman 1990, Wang & Gartung 2010, Ballester et al 2013. Therefore, the Tc of crops might be more sensitive to severe drought stress in the irrigation treatments.…”
Section: Interannual Variations In Tc-tamentioning
confidence: 99%
See 2 more Smart Citations